Aligning Stakeholder Frames for Transition Management in Solid Waste: A Case Study of Bangalore - Nivedita Biyani; Manisha Anantharaman (Revue Internationale de Politique de Développement)
Increasingly, sanitation issues are becoming a central part of global environmental governance and the discourse on sustainability. The city of Bangalore, India, is one of many cities worldwide that is trying to come to terms with its solid waste management (SWM) problems. In 2000, the Government of India issued SWM handling rules, which is a non-binding handbook (MSW Rules 2000) that seeks to guide state and city municipalities and stakeholders in their efforts to deliver better services. A serious SWM crisis prompted Bangalore to be the first city in India to mandate segregation of waste at source. However, implementing these mandates has been a slow process, for reasons we explore in this paper. Building on transition management scholarship, the paper examines the role of interpersonal competency and framing in facilitating partnerships between diverse actors. We do this by i) clarifying the motives of actors and their aims and frames; ii) understanding roles, needs and skills; and iii) selecting, from communication research, communication methods that could possibly secure an enduring shift to more sustainable SWM policies. Our analysis shows that i) the drivers and objectives of some of the actors involved are not coherent with the main vision of the government, and ii) some actors in the city’s SWM field stand to lose financially because of the new mandates, and hence strongly oppose the change. Role transformations would need diverse stakeholders in Bangalore’s SWM system to come together for a cleaner city. This paper focuses on framing and facilitation strategies in the transitional arena for better participatory governance and stakeholder engagement.